AGRICULTURAL GROWTH RESPONSE TO HUMAN CAPITAL DEVELOPMENT IN NIGERIA - Udeme Henrietta UKPE; Jacintha Nkeiruka EZE; Fani Raoul Choumbou DJOMO; Chinwe Prisca OSAYI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This study evaluated agricultural growth response to human capital development in Nigeria. Annual time series data covering a period of 1993-2017 were utilized to analyse the objectives. The result shows that recurrent expenditure on education contributed above 10% and capital expenditure on education contributed above 2% to agricultural growth in the long run. Primary school enrolment contributed above 20% and tertiary institution enrolment contributed above 1% to agricultural growth in the short run. The impulse response result shows that agricultural growth responded negatively capital expenditure on education but responded significantly to recurrent expenditure. There was minimal response of agricultural growth to both capital and recurrent expenditures on health. It was therefore recommended that capital expenditures on education and health be increased and channelled appropriately.